Latent Hydraulic Effect of Ground Granulated Blast Furnace Slag on the Strength Development of Stabilized Peat - Wong L.S.; Alhaddad H.O.A.; Bakri R.S.A.B.; Haider H.A.A.; Oweida A.F.M. (Springer Nature, 2025)
Peat is identified as soft organic soil with high water retention. It cannot be stabilized with Portland cement for soil improvement due to its impediment to cement hydrolysis. Hence, there is a need to explore suitable additives for effective peat stabilization. This study sampled tropical peat from Sri Nadi village in Malaysia before being transported to the laboratory for testing. Ground granulated blast furnace slag (GGBS) and Portland composite cement (PCC) were investigated as peat additives for stabilization purposes. The PCC had 4% calcium chloride and 2% polycarboxylate superplasticizer by weight of the cement. Calcium chloride and polycarboxylate superplasticizer acted as cement accelerators and workability-enhancing agents for stabilizing the peat. The latent hydraulic effect of GGBS was evaluated by varying its content from 0 to 15% of PCC in the mix designs of stabilized peat specimens. After curing, each test specimen was crushed until failure in an unconfined compression test. It was discovered that a mix design of 300kgm?3 binder dosage (90% PCC: 10% GGBS) and 596kgm?3 river sand dosage is optimal for stabilizing the soil. The test specimen?s 90days unconfined compressive strength and elastic modulus were 573 and 11,750kPa, respectively. The unconfined compressive strength was higher than the minimum strength value of 345kPa required for effective soil stabilization. The key findings are enormously impactful on the mass stabilization of peat at construction sites. ? The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.